2020
DOI: 10.1186/s12886-020-01413-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and multiple sub-internal limiting membrane hemorrhages in a familial retinal arteriolar tortuosity patient by Valsalva-like mechanism: an observational case report

Abstract: Background: Bilateral and multiple Valsalva-related sub-internal limiting membrane (ILM) hemorrhages in a familial retinal arteriolar tortuosity (FRAT) patient is rare, and we treated this patient by both observation and Neodymium yttrium aluminum garnet (Nd: YAG) laser membranotomy methods. Case presentation: A 13-year-old female student presented with sudden visual loss and central scotoma in both eyes after running 800 m at the school gym. The examination revealed six sub-ILM hemorrhages with the biggest he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In most cases as in the current case, the clinical picture improves without treatment, 2 , 11 , 13 , 14 but if the hemorrhages are bilateral or the visual loss is severe, treatment is considered. Chen et al 15 performed Nd:YAG laser membranotomy to treat sub-ILM hemorrhage at the macula in a patient with FRAT and reported that the treatment was effective when rapid visual recovery is needed due to bilateral sub-ILM hemorrhages at the macula.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases as in the current case, the clinical picture improves without treatment, 2 , 11 , 13 , 14 but if the hemorrhages are bilateral or the visual loss is severe, treatment is considered. Chen et al 15 performed Nd:YAG laser membranotomy to treat sub-ILM hemorrhage at the macula in a patient with FRAT and reported that the treatment was effective when rapid visual recovery is needed due to bilateral sub-ILM hemorrhages at the macula.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite common in daily life and typical activities such as coughing hard, vomiting, straining, constipation, and weightlifting can all lead to it [ 6 ]. The Valsalva maneuver can affect retinal arteries due to the sudden and violent fluctuation of blood pressure that occurs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%